LEGAL STANDING KURIR EXPEDISI MENGIRIM BARANG BERUPA NARKOTIKA KARENA TIDAK MENGETAHUI - Nuryanta, Gede Agung Raynanda Putra; Mahyani, Ahmad (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Along with the development of technology, it makes it easier for humans to find information in various things that exist in the digital era or the current era and the advancement of telecommunication technology eliminates distance and the world becomes borderless world. Conventional buying and selling itself has been done since ancient times and with it developments that there is buying and selling is experiencing developments where buying and selling in the current era which we usually call the E-Commerce buying and selling system, the development of buying and selling is a person or seller who is in the online buying and selling application selling as well as possible, one of which is narcotics which has been described in Law 35 of 2009 on the Narcotics Law Article 1 paragraph 1 states that narcotics are artificial substances or those derived from plants that have hallucinatory effects, decrease consciousness, and cause addiction. These drugs can cause addiction if used excessively. The use of these substances is as a painkiller and provides calm. Abuse can be subject to legal sanctions. A person who buys narcotics via E-commerce where there is no sanction that ensnares the seller in the Buying and Selling Application they sell narcotics with indications of male strong drugs, in this problem In the Narcotics Act itself there are which elements for those who know or do not know can be subject to criminal penalties, because in their duties the sender of goods or couriers who carry out their duties can be punished based on the Narcotics Law, therefore the author wants to research related to Legal Arrangements on Expeditionary Couriers who carry out their work